Formal-Logical and Methodological Examination of Scientific Theories - Meškauskas, Eugenijus (Problemos, 1989)
The cognitive status of formal-logical and methodological examination of scientific theories is discussed. In the first case a theory is considered as a closed whole. Its suitability as a theoretical model of reality is established on the base of the given empirical data. In the second case a theory is analysed for its perspectives in further research. In the view of dialectical materialism the two types of examination are interconnected and in no way contradict each other.